PKM Sosialisasi Penggunaan Aplikasi Canva Dalam Pembuatan E-Presentation Untuk Adminitrasi di RT 004/003 Kelurahan Cipayung - Retna Ningsih; Dewi Mustari; Theresia Evy Yulianty Nadeak (Lembaga Pengembangan Kinerja Dosen, 2024)
This activity is community service which is included in the IbM scheme which is held with financial support from the Institute for Research and Community Service (LPPM) Indrapratas University PGRI for the 2023/2024 even semester academic year. This Community Service is the participation of Indraprasta PGRI University in order to help one element of society in the field of education, especially the residents of RT 04 RW 03, Cipayung Village, East Jakarta. When today's increasingly sophisticated technology is used for positive and useful things. Therefore, electronic presentations are currently very helpful in administrative work. Electronic presentations are presentation documents created using various tools such as PowerPoint, Canva, which are very useful in giving presentations to RT level government officials in RW 03, Cipayung, East Jakarta. The use of Canva e-presentation in terms of presenting various activities or administrative reporting to residents of RT 04 Rw 03, Cipayung sub-district. Therefore, the community service team, TEAM Lecturers from Indraprasta PGRI University will provide outreach regarding how to use Canva for E-Presentation for administration.